Portuguese Adaptation of Students Engagement in Schools International Scale (Sesis) - Melo, Madalena (2013)
The importance of student’s engagement has been recently pointed out in research. However, there has been a lack of engagement assessment instruments, showing psychometric qualities, such as reliability and validity. Objective: This paper presents the Portuguese adaptation of the “Student’s Engagement in Schools International Scale” (SESIS), drawn up from 12 countries international study (Lam et al., 2012; Lam et al., in press). Method: Psychometric properties of this scale were examined using data from 685 students, of both sexes, and from different grades (6th, 7th, 9th and 10th), and regions of the country. Results: Factorial analysis of the results, with varimax rotation, conducted to three different factors which explain 62,19% of the variance. The scale integrates the original 33 items, and cognitive, affective and behavioural dimensions. For the external validity study, the relationship between student’s engagement in school results and other school variables — academic performance, school conduct — was considered, and significant relations were observed, as expected. Conclusion: The data presented highlights the qualities of SESIS, as well as its usefulness for research purpose. Suggestion: It is suggested the investigation of the extension of SESIS’s three-dimensionality, in future studies